2019
DOI: 10.1145/3306346.3322966
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biologically realistic human motion using joint torque actuation

Abstract: Using joint actuators to drive the skeletal movements is a common practice in character animation, but the resultant torque patterns are often unnatural or infeasible for real humans to achieve. On the other hand, physiologicallybased models explicitly simulate muscles and tendons and thus produce more human-like movements and torque patterns. This paper introduces a technique to transform an optimal control problem formulated in the muscleactuation space to an equivalent problem in the joint-actuation space, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 76 publications
(60 reference statements)
1
51
0
Order By: Relevance
“…[PALvdP18, MAP * 18]. In our experiments, we find, as in [JVWDGL19], that natural motion is easier to achieve with the use of realistic torque limits.…”
Section: Character Modelssupporting
confidence: 71%
“…[PALvdP18, MAP * 18]. In our experiments, we find, as in [JVWDGL19], that natural motion is easier to achieve with the use of realistic torque limits.…”
Section: Character Modelssupporting
confidence: 71%
“…Previously, it was shown that using algorithmic derivatives is faster than finite differences which are used by OpenSim 43 . Machine learning approaches were recently investigated in the field of computer graphics to speed up musculoskeletal simulation 44 , 45 . Jiang et al 44 learned a mapping from muscle-actuation space to joint-actuation space which would have to be retrained if model parameters are changing.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning approaches were recently investigated in the field of computer graphics to speed up musculoskeletal simulation 44 , 45 . Jiang et al 44 learned a mapping from muscle-actuation space to joint-actuation space which would have to be retrained if model parameters are changing. Lee et al 45 used a two-stage deep reinforcement learning approach to simulate a full-body 3D musculoskeletal model.…”
Section: Discussionmentioning
confidence: 99%
“…In biomechanics, some RL-based solutions have been introduced for the motor control tasks either via muscle activations (Abdi et al, 2019b) or joint activations (Clegg et al, 2018). In human locomotion, most works have focused on arm movement (Golkhou et al, 2005;Jagodnik et al, 2016) and gait control (Peng et al, 2017;Kidziński et al, 2018;Jiang et al, 2019). Recent interdisciplinary collaborations have helped to bridge the gap between reinforcement learning and motor control in biomechanics using the OpenSim and ArtiSynth modeling environments (Kidziński et al, 2018;Abdi et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%